Games-Based Learning: Konsep Pengajaran Literasi Informasi Berbasis Permainan pada Mahasiswa Strata 1 di Universitas Pelita Harapan - HW, Phillips Iman (UI Scholars Hub, 2019)
Games-based learning is a new concept that is used for teaching information literacy skills, which so far has been mostly given in classrooms and is one-way. The respondents taken were all new students participating in games-based learning activities, in 2018. In the implementation of games-based learning divided into 5 posts, where each post represents one information literacy skill material. The results are as follows identification of information (3.46), access to information (3.59), using information (3.36), synthesis (3.52) and plagiarism (3.55). With a total average of 3.47 while the average results of the level of collaboration and creativity obtained by 3.54. The conclusion is that students participating in this activity are very enthusiastic and happy so they can easily understand the material provided.